Platform-based BST-2-targeted microbubbles enhance HIFU therapy and effectively inhibit prostate cancer residual growth - Hang Zhou; Jia Tang; Yujie Wan; Jiaqi Gong; Qizhi Wang; Kaifeng Huang; Ruixia Hong; Xinzhi Xu; Fang Li (International Journal of Hyperthermia)
Objective This study aims to evaluate the potential of BST2-targeted microbubble-facilitated HIFU therapy for prostate cancer (PCa), and to elucidate the mechanisms of synergistic tumor suppression in residual lesions.Methods The specificity of BST-2 expression in PCa tumor endothelial cells was established using a cellular co-culture method. The targeting efficacy of Anti-BST-2 antibody-conjugated microbubbles (BST-2-MB) was evaluated both in vitro and in vivo. The therapeutic outcomes of BST-2-MB-augmented HIFU (High-Intensity Focused Ultrasound) for PCa in Balb/c mice were compared with those of non-targeted microbubbles and HIFU alone. Changes in the immunological microenvironment and modulation of BST-2-related oncogenic pathways in residual tumors were analyzed using Western Blot, immunofluorescence, flow cytometry, and ELISA.Results BST-2 is highly expressed in PCa vascular endothelial cells, and BST-2-MBs show strong targeting efficacy. HIFU combined with BST-2-MB achieved larger ablation volumes and potent inhibition of residual tumor growth. This treatment induced more immunogenic cell death (ICD), DC maturation, and CD8+ T cell infiltration, and significantly downregulated the expression of BST-2, EGFR, pSTAT3, and pErk1/2 compared to other treatments.Conclusion BST-2-MB combined with HIFU therapy demonstrates a superior synergistic antitumor effect in PCa, effectively inhibiting residual tumors, which offers a novel strategy to enhance HIFU efficacy.